Changes in adenosine 5'-monophosphate-activated protein kinase as a mechanism of visceral obesity in Cushing's syndrome. - Kola, B; Christ-Crain, M; Lolli, F; Arnaldi, G; Giacchetti, G; Boscaro, M; Grossman, AB; Korbonits, M (2008)
OBJECTIVE: Features of the metabolic syndrome such as central obesity with insulin resistance and dyslipidemia are typical signs of Cushing's syndrome and common side effects of prolonged glucocorticoid treatment. AMP-activated protein kinase (AMPK), a key regulatory enzyme of lipid and carbohydrate metabolism as well as appetite, is involved in the development of the deleterious metabolic effects of excess glucocorticoids, but no data are available in humans. In the current study, we demonstrate the effect of high glucocorticoid levels on AMPK activity of human adipose tissue samples from patients with Cushing's syndrome. METHODS: AMPK activity and mRNA expression of genes involved in lipid metabolism were assessed in visceral adipose tissue removed at abdominal surgery of 11 patients with Cushing's syndrome, nine sex-, age-, and weight-matched patients with adrenal incidentalomas, and in visceral adipose tissue from four patients with non-endocrine-related abdominal surgery. RESULTS: The patients with Cushing's syndrome exhibited a 70% lower AMPK activity in visceral adipose tissue as compared with both incidentalomas and control patients (P = 0.007 and P < 0.001, respectively). Downstream targets of AMPK fatty acid synthase and phosphoenol-pyruvate carboxykinase were up-regulated in patients with Cushing's syndrome. AMPK activity was inversely correlated with 0900 h serum cortisol and with urinary free cortisol. CONCLUSIONS: Our data suggest that glucocorticoids inhibit AMPK activity in adipose tissue, suggesting a novel mechanism to explain the deposition of visceral adipose tissue and the consequent central obesity observed in patients with iatrogenic or endogenous Cushing's syndrome.